REPRESENTASI KELAS SOSIAL DALAM RUANG TEKS JALANAN - Rosa, Dien Vidia (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
The streets could be read as space all at once medium which full of social class representation. Through representation, text were not only seen as signs that had polisemic meaning but it was more as power contestation space where signs dominated each other. Media and text representation could appeared everywhere even in the hidden or careless rooms as toilets. This article which was a literature study discussed text that attached on vehicles such as cars and trucks. Each text showed the signs relation game in different social class and space which however met in the streets. In the space of streets, power context refered to subject that disseminated text and formed representation discourse.